Genomic characterization of Escherichia coli with a polyketide synthase (pks) island isolated from ulcerative colitis patients - Chao Lv; Mohd Abdullah; Chun-Li Su; Weiye Chen; Nan Zhou; Zile Cheng; Yiwen Chen; Min Li; Kenneth W. Simpson; Ahmed Elsaadi; Yongzhang Zhu; Steven M. Lipkin; et al. (BMC Genomics)
Abstract The E. coli strains harboring the polyketide synthase (pks) island encode the genotoxin colibactin, a secondary metabolite reported to have severe implications for human health and for the progression of colorectal cancer. The present study involves whole-genome-wide comparison and phylogenetic analysis of pks harboring E. coli isolates to gain insight into the distribution and evolution of these organisms. Fifteen E. coli strains isolated from patients with ulcerative colitis (UC) were sequenced, 13 of which harbored pks islands. In addition, 2,654 genomes from the public database were also screened for pks harboring E. coli genomes, 158 of which were pks-positive (pks + ) isolates. Whole-genome-wide comparison and phylogenetic analysis revealed that 171 (158 + 13) pks + isolates belonged to phylogroup B2, and most of the isolates belong to sequence types ST73 and ST95. One isolate from a UC patient was of the sequence type ST8303. The maximum likelihood tree based on the core genome of pks + isolates revealed horizontal gene transfer across sequence types and serotypes. Virulome and resistome analyses revealed the0020preponderance of virulence genes and a reduced number of antimicrobial genes in pks + isolates. This study significantly contributes to understanding the evolution of pks islands in E. coli.